Pelvic floor muscle training in women with a history of breast cancer - Inna A Apolikhina; Valerii V Rodionov; Anna S Seialova; Aina S Saidova; Irina A Gukasian (IP Berlin A.V., 2019)
Relevance. The issue of pelvic floor muscle dysfunction (PFMD) is common in female population. It causes severe moral suffering and reduces both social activity and a quality of patient's life. In this regard PFMD management with modern methods for training of pelvic floor muscles using devices is the "first line" method. Aim. To study treatment effectiveness and a quality of life in women with PFMD followed radical treatment for breast cancer (BC). Outcomes and methods. A prospective clinical study on clinical efficacy of a biofeedback method in combination with electrical stimulation of pelvic floor muscles using a device "Urostim" in patients with mild PFMD followed combined treatment fpr BC was carried out at Department of Aesthetic Gynecology of V.I.Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology. The study included 15 postmenopausal women. Results. It was established that 10 sessions of pelvic floor muscles training in a mode of biofeedback result in beneficial effects on for all clinical indicators. Conclusion. PFMD treatment by training of pelvic floor muscles using devices is one of the most promising ways to reduce surgical interventions number in urogynecology and to provide a rehabilitation of women who had surgery for BC.